2021
DOI: 10.3390/plants10040770
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Cadmium in Early-Diverging Streptophytes (Charophytes and Bryophytes): Current Views and Potential Applications

Abstract: Several transition metals are essential for plant growth and development, as they are involved in various fundamental metabolic functions. By contrast, cadmium (Cd) is a metal that can prove extremely toxic for plants and other organisms in a dose-dependent manner. Charophytes and bryophytes are early-diverging streptophytes widely employed for biomonitoring purposes, as they are able to cope with high concentrations of toxic metal(loid)s without showing any apparent heavy damage. In this review, we will deal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 170 publications
0
11
0
Order By: Relevance
“…The results of this study showed that GSH application induced the uptake and accumulation of Cd in the roots and shoots of B. napus , while it alleviated the overall growth inhibition caused by Cd toxicity, subsequently indicating GSH-induced improvement in Cd tolerance. Furthermore, GSH functions as a Cd chelator, leading to the formation of Cd-GSH complexes that promote Cd uptake through the roots and enhance Cd accumulation in the vacuole (Seth et al, 2012 ; Anjum et al, 2014 ; Ding et al, 2017 ; Bellini et al, 2021 ). In addition, phytochelatins (PCs), which are GSH-derived polypeptides produced by PC synthase, chelate with Cd to form PCs-Cd complexes in the cytosol, which are then transported and sequestered into the vacuoles through ATP-binding cassette (ABC) transporters, thereby inducing the detoxification of Cd in plant cells (Ueno et al, 2010 ; Yadav, 2010 ; Park et al, 2012 ; Zagorchev et al, 2013 ; Semida et al, 2018 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that GSH application induced the uptake and accumulation of Cd in the roots and shoots of B. napus , while it alleviated the overall growth inhibition caused by Cd toxicity, subsequently indicating GSH-induced improvement in Cd tolerance. Furthermore, GSH functions as a Cd chelator, leading to the formation of Cd-GSH complexes that promote Cd uptake through the roots and enhance Cd accumulation in the vacuole (Seth et al, 2012 ; Anjum et al, 2014 ; Ding et al, 2017 ; Bellini et al, 2021 ). In addition, phytochelatins (PCs), which are GSH-derived polypeptides produced by PC synthase, chelate with Cd to form PCs-Cd complexes in the cytosol, which are then transported and sequestered into the vacuoles through ATP-binding cassette (ABC) transporters, thereby inducing the detoxification of Cd in plant cells (Ueno et al, 2010 ; Yadav, 2010 ; Park et al, 2012 ; Zagorchev et al, 2013 ; Semida et al, 2018 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liverworts are known for their ability to accumulate heavy metals in high concentrations through chelation and passive ion exchange mechanisms [5,7]. Their large surface/volume ratio allows them to efficiently absorb water and dissolved elements from the entire surface of the gametophyte [37].…”
Section: The Extraction Procedures and The Analytical Methods Used Al...mentioning
confidence: 99%
“…Stresses 2022, 2 137 In particular, bryophytes (including Marchantiophyta, Bryophyta and Anthocerotophyta) might prove to be useful model organisms for gaining a better understanding of metal accumulation and detoxification processes in plants [5,7]. Due to their poikilohydric nature, bryophytes do not possess strong hydrophobic barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have ruled out the possibility of using the moss Ptychostomum capillare in biomonitoring of air pollution due to a defense mechanism mediated by lipophilic substances (probably waxes) that act as a barrier to prevent metal from entering the cells, which could distort direct estimates of environmental copper content through levels detected in its tissues [ 23 ]. Thus, understanding the effects of analytes on bryophyte morphophysiological traits may be fundamental to optimizing their use in biomonitoring [ 24 ]. Therefore, in addition to just studying the surface sorption of trace elements by mosses, it is necessary to focus on the bioconcentration of these elements in their interior, and look for relationships between particles attached to the surface and those bioaccumulated in their tissues [ 12 ].…”
Section: Introductionmentioning
confidence: 99%